Disaster Management in the Public Administration System of NC - Iscioglu, Deniz; Keles, Rusen (Int Information Inst, 2011)
In this research, disaster management is being analyzed according to public administration system of Northern Cyprus. The aim of the research is to analyze the disaster management in North Cyprus (NC) deeply and to determine the problems in this area. We are going to discuss whether there is an effective disaster management in NC by analyzing the results of the researches that were done. According to the objective of the research, the main focus shall be disaster management and disaster management planning. Then, the laws and other related legislations in NC about emergency situation and disaster management will be analyzed. In the next chapter, we will try to evaluate the disaster management applications. Through this, the disaster management in NC will be considered thoroughly and it will be questioned whether there is an effective management in NC. In the conclusion, the problems of NC's disaster management will be evaluated and a general assessment will be done.
Keywords: Disaster Management; Public Administration; Disaster Management in North Cyprus